2022
DOI: 10.21462/jeltl.v7i3.852
|View full text |Cite
|
Sign up to set email alerts
|

Post-Graduate Students’ Perceptions of Quillbot Utilization in English Academic Writing Class

Abstract: <em>Academic writing is currently a worldwide concern. A plethora of studies on academic writing difficulties in higher education has been conducted. With the advancement of technology, the challenges of academic writing can be alleviated by using Quillbot, an artificial intelligence (AI)-powered digital tool. However, research on using Quillbot in post-graduate academic writing classrooms is still limited, and little is known about how students perceive it. This study investigates how post-graduate stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 20 publications
11
48
0
Order By: Relevance
“…Paraphrasing skills, being one of the most important components of the technical writing syllabus, need special efforts on part of students to improve it so that they can improve on paraphrasing skills as well as score good marks in examination. The results are consistent with another study by Kurniati and Fithriani (2022), who found that the post-graduate students in this study had a favorable reaction to utilize QuillBot to help them improve the level of their writing. They mentioned that QuillBot had three advantages: improving students' favorable attitudes about writing, offering a multiplicity of comprehensible writing tools, and encouraging the language development of students.…”
Section: Discussionsupporting
confidence: 92%
“…Paraphrasing skills, being one of the most important components of the technical writing syllabus, need special efforts on part of students to improve it so that they can improve on paraphrasing skills as well as score good marks in examination. The results are consistent with another study by Kurniati and Fithriani (2022), who found that the post-graduate students in this study had a favorable reaction to utilize QuillBot to help them improve the level of their writing. They mentioned that QuillBot had three advantages: improving students' favorable attitudes about writing, offering a multiplicity of comprehensible writing tools, and encouraging the language development of students.…”
Section: Discussionsupporting
confidence: 92%
“…Because in an era of rapid technological advancement, numerous technologies can facilitate human labor, particularly the activity of lecturers in teaching and learning. The use of digital technologies assisted by artificial intelligence (AI) in writing classes, such as quillbot, grammarly, and Facebook, is trusted by students as a platform for evaluating their work and has numerous benefits that help improve student writing quality Ginting & Fithriani, 2022;Kurniati & Fithriani, 2022). With the aid of technology tools, students can easily and quickly receive feedback and corrections, reducing the number of errors that need to be examined again by the lecturer.…”
Section: Discussionmentioning
confidence: 99%
“…Quillbot was believed to be applicable for L2 writing with a variety of functions and a balance between technology and human intelligence (Fitria, 2022). In a recent study examining the effects of QuillBot on post-graduate students' performance in academic writing, students expressed positive attitude towards the adoption of the application as an assistant for high quality writing (Kurniati & Fithriani, 2022).…”
Section: Technology-enhanced L2 Writing: New Trends In the Age Of Aimentioning
confidence: 99%
“…Particularly, the introduction of tools and applications based on artificial intelligence (AI) have brought about paradigmatical changes to technology-enhance L2 writing. Tools such as Grammarly (Koltovskaia, 2020), Quillbot (Kurniati & Fithriani, 2022), Google Translate (Cancino & Panes, 2021) have significantly automated the workflow of writing, assessment, proofreading, etc.…”
Section: Introductionmentioning
confidence: 99%